Strategi Pemasaran Produk Kerajinan Eceng Gondok Di Desa Banyu Hirang Kecamatan Amuntai Selatan Kabupaten Hulu Sungai Utara (Studi Kasus Kelompok Usaha Bersama (KUB) “ Kembang Ilung”) - Yani Warliyanti (Rawa Sains: Jurnal Sains STIPER Amuntai, 2012)
This study aims (i) to know the strength, weaknesses, threats and opportunities, and (ii) to find out how the marketing strategy of the "Kembang Ilung" Joint Business Group (KUB) in Banyu Hirang Village, Hulu Sungai Utara Regency. The case method is used in this study, there are two parties who are respondents, namely the internal party is the manager of the KUB and the member is the water hyacinth craftsman, while the external party is Disparindagkop. Hulu Sungai Utara Regency. The results showed that the IFE matrix was 2.592 and the EFE matrix was 2.674 where the IE matrix placed the Kembang Ilung in the V quadrant, namely the Hold and Maintain strategy (keep and maintain). The strategy that can be applied to this position is the strategy of market penetration and product development.